Spin-outs' knowledge legacies and parent hostility: a competitive dynamics view - Sascha G. Walter (Small Business Economics, 2023)
This study adopts a competitive dynamics perspective to illuminate how and when different types of knowledge transferred by a spin-out trigger parent hostility. Specifically, I propose based on the awareness-motivation-capability framework that (1) transfers of market-related and technology-related knowledge will yield hostility and that (2) market commonality, resource similarity, and competitive intensity will exacerbate this effect. Findings from 207 spin-outs support several of my hypotheses. The study contributes to the extant literature by providing a more nuanced view on knowledge legacies, in particular regarding their interplay with a spin-out's competitive positioning.
Keywords: L26; M13; 330; Spin-outs; Knowledge; Entrepreneurship; New venture strategies; Strategy